Characteristics, Demographics and Malnutisi of Toddlers in West Papua Province - Citra Justicia Emryssyah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2021)
Background: Malnutrition is a problem that occurs in several Indonesian provinces. West Papua Province is one of the provinces where malnutrition occurs. The high incidence of malnutrition will play an important role in human resources so that it will have a major impact on the low generation of the nation in West Papua Province. This study aims to determine the risk factors for malnutrition in West Papua Province. Methods: This study uses a secondary analysis of 2018 Basic Health Research data in West Papua Province. The number of samples in this study were 159 babies aged 0-23 months. Measurements using anthropometry with weight /age. Data analysis used cross tabulation descriptive analysis. Results: The results of this study showed that there were 107 infants under two years of age who suffered from malnutrition (16.7%) and infants under two years of age who had normal nutrition as many as 534 babies (83.3%). There was no significant difference between sex and age of malnourished infants. There was a relationship between the education of the head of the household (p <0.001), the occupation of the head of the household and the incidence of malnutrition among infants in West Papua Province.Conclusion: Malnutrition cases occur in infants under two years of age with sociodemographic conditions with low education of the head of the household, the head of the household does not work, and lives in rural areas. Health workers in West Papua Province must be more intense in educating heads of households with low education and low income about dietary consumption and parenting patterns in order to reduce the incidence of malnutrition in infants under two years of age.